Allogeneic Articular Chondrocyte Transplantation Downregulates Interleukin 8 Gene Expression in the Degenerating Rabbit Intervertebral Disk In Vivo. (July 2015) - Zhang, Yejia; Chee, Ana; Shi, Peng; Wang, Rui; Moss, Isaac; Chen, Er-Yun; He, Tong-Chuan; An, Howard S.
ABSTRACT: Objective: The aim of this study was to investigate whether repopulating the degenerating intervertebral disk (IVD) with articular chondrocytes will decrease inflammation in the degenerating rabbit IVD. Design: This was a biologic study in a rabbit IVD-injury model in vivo. Dual cell tracking methods (infrared dye labeling and adenovirus transduction) were used to demonstrate the viability of allogeneic articular chondrocytes injected into degenerating rabbit IVDs. Interleukin 8 gene expression was determined via real-time polymerase chain reaction. Infiltrating inflammatory cells (macrophages, T cells, or neutrophils) were examined with immunohistochemistry. The IVDs were also examined by routine histology. Results: Articular chondrocytes labeled with infrared dye were detected in the degenerating IVDs at both 2 and 8 wks after injection. At the 2-wk time point, interleukin 8 gene expression was comparable in IVDs injected with chondrocytes and in intact disks as control ( P = 0.647), whereas its expression in IVDs injected with saline increased 50-fold ( P = 0.028). Transgene expression of red fluorescent protein, β-galactosidase, and human bone morphogenetic protein 7 diminished at 8 wks after injection. IVDs injected with chondrocytes overexpressing human bone morphogenetic protein 7 did not show lower interleukin 8 gene expression or improved histology. Macrophages were consistently detected by immunohistochemistry in the cartilage formed around the needle insertion sites in both the saline and chondrocyte groups, whereas neither T cells nor neutrophils were detected. Conclusions: Allogeneic rabbit articular chondrocyte survived in the degenerating rabbit IVDs for at least 8 wks. Cell treatment resulted in reduced IVD inflammation but did not significantly improve IVD structure.